Outcome of pars plana vitrectomy with pre-operative intra vitreal bevacizumab in diabetic patients with vitreous haemorrhage - Mustafa, Alina; Siddiq, Saqib; Shahbaz, Maha; Ihsan, Khawaja Mohsin; Shah, Syed Raza Ali; Waheed, Khalid (Journal of Fatima Jinnah Medical University, 2022)
Background: Intravitreal bevacizumab causes regression of retinal neo vessels in proliferative diabetic retinopathy as it is anti-vascular endothelial growth factor (anti VEGF). So this study was done to observe the effect of pre-operative intravitreal bevacizumab on intra operative outcome when administered in patients with vitreous hemorrhage undergoing pars-plana vitrectomy (PPV). Patients and methods: This quasi-experimental trial was carried out in the Department of Ophthalmology Services Hospital Lahore from June 2020 to December 2020. Fifty seven diabetic patients with vitreous hemorrhage were selected who were eligible for PPV. Patients with recurrent hemorrhage were not included. Demographics were recorded and all patients were given intravitreal bevacizumab (1.25 mg/0.05 ml) one week prior to vitrectomy and intra-operative bleeding was noted. Intra-operative bleeding was graded as No, Mild and Severe bleeding. Results: The mean age of patients undergoing PPV was 55.36 ± 4.62 years. There were 35 (61%) males and 22 (39%) females. The mean duration of diabetes was 10.35±1.92 years. Out of 57 eyes, 36 (63.15%) had no bleeding, 11 (19.29%) had mild and 10 (17.54%) had severe intra-operative bleeding. Conclusion: Intravitreal bevacizumab prior to PPV is quite effective in reducing the risk of intra-operative bleeding in patients with vitreous hemorrhage.